Exploring the role of LOX family in glioma progression and immune modulation - Chen Liu; Chen Liu; Chen Liu; Huilian Qiao; Hongqi Li; Xiaolong Hu; Maohui Yan; Zhiguang Fu; Hengheng Zhang; Yingjie Wang; Nan Du; Nan Du (Frontiers in Immunology)
BackgroundGlioma is a major cause of mortality among central nervous system tumors, with a generally poor prognosis. The lysyl oxidase (LOX) family, a group of copper-dependent amine oxidases, has been implicated in the progression of various cancers, but its specific role in glioma and its relationship with immune infiltration remains insufficiently explored. This study aims to investigate the LOX family’s expression, prognostic significance, and immune infiltration dynamics in glioma to identify potential therapeutic targets.MethodsA comprehensive analysis was conducted using public databases to assess gene expression, mutation frequency, and immune infiltration patterns related to the LOX family in glioma. The results were validated through survival analysis and immunohistochemistry. Functional assays, including EdU, Transwell, and flow cytometry, were used to evaluate glioma cell proliferation, migration, invasion, and apoptosis. Co-culture experiments with immune cells, ELISA, and a glioma transplantation model were employed to study the immune-modulatory effects of the LOX family. Gene and protein expression levels were further analyzed using qRT-PCR and Western blotting.ResultsThe LOX family was significantly upregulated in low-grade gliomas and strongly associated with poor clinical outcomes. Although mutation frequencies were low, the LOX family contributed to glioma progression through pathways involving metastasis, hypoxia response, angiogenesis, and immune cell infiltration. LOX expression correlated with increased infiltration of macrophages and eosinophils and decreased presence of Treg and CD8+ T cells. Knockdown of LOX genes impaired glioma cell functions, induced apoptosis, and altered immune cell behavior by reducing M2 macrophage polarization and enhancing CD8+ T cell activity.ConclusionsThe LOX family is overexpressed in glioma and is associated with poor prognosis and altered immune infiltration patterns. These findings highlight the LOX family as a promising prognostic marker and therapeutic target, particularly for enhancing the effectiveness of immunotherapy in glioma treatment.